A numerical study of the influence of Z-pin parameters on the elastic properties of laminates. Issue 9 (November 2021) - Li, Mengjia; Chen, Puhui
A finite element model with periodic boundary conditions was developed to investigate the influence of different Z-pin parameters including diameter, spacing, and insertion angle of Z-pin on the elastic properties of composite laminates. Benchmark tests were carried out to verify the FE model and a series of parametric analyses were subsequently performed. In general, all the elastic moduli, excluding the through-thickness modulus ( Ez ), decreased while Ez increased nonlinearly with increasing Z-pin diameter and decreasing spacing. The reduction of Ey (transverse modulus) was approximately 40% of that of Ex (longitudinal modulus), while the reduction of Gxy is similar to that of Ex . Besides, Gxz and Gyz were reduced by approximately half of the reduction of Gxy . Although the impact of insertion angle was obvious on Ez, it was negligible on the other five moduli.